2020
DOI: 10.1136/bmj.m3048
|View full text |Cite
|
Sign up to set email alerts
|

Adversity in childhood is linked to mental and physical health throughout life

Abstract: The prevalence of “toxic stress” and huge downstream consequences in disease, suffering, and financial costs make prevention and early intervention crucial, say Charles A Nelson and colleagues

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
312
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 385 publications
(331 citation statements)
references
References 68 publications
10
312
2
7
Order By: Relevance
“…Childhood exposure to adverse childhood events (ACEs) and pathways to adult outcomes (from Nelson, et al Adversity in childhood is linked to mental and physical health through life. BMJ 2020, 371, m3048 [43]…”
mentioning
confidence: 99%
“…Childhood exposure to adverse childhood events (ACEs) and pathways to adult outcomes (from Nelson, et al Adversity in childhood is linked to mental and physical health through life. BMJ 2020, 371, m3048 [43]…”
mentioning
confidence: 99%
“…The model links together a diverse set of individual-level life outcomes of interest to policymakers (see Figure 1). In choosing the model outcomes and formulating the model structure we consulted with experts in childhood development and childhood policy, demography, epidemiology, human capital economics and labour economics (see list of advisory group members in the acknowledgements) and were also guided by inter-disciplinary theory on human capital formation in childhood and how this influences educational attainment, earnings, physical illness, mental illness, mortality and other outcomes with important impacts on individual wellbeing and public cost (Almond, Currie and Duque, 2018; Goodman et al, 2015; Nelson et al, 2020; Cunha and Heckman, 2010; Adler and Stewart, 2010; O’Donnell, Van Doorslaer and Van Ourti, 2015; Layard et al, 2014; Shonkoff, 2010; Black et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, it remains to be investigated how far-reaching the herein observed negative effects on well-being are. Past work has indicated that early adversities can have an impact for life, with effects potentially being most significant in younger age and depending on the intensity of the experience (Nelson et al, 2020). An increased understanding of protective and/or risk factors and mechanisms leading to the development of stress-related psychopathologies may ultimately hold the potential to facilitate more personalized prevention and treatment strategies.…”
Section: Limitations and Further Considerationsmentioning
confidence: 99%